2015
DOI: 10.1007/s00421-015-3230-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between muscle sympathetic nerve activity and aortic wave reflection characteristics in aerobic- and resistance-trained subjects

Abstract: These results confirm previous reports of a positive association between MSNA and AIx in young male resistance-trained subjects. Furthermore, RT is associated with increased arterial stiffness and elevated sympathetic outflow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…activity, oxidative, or endothelial function for this study, which would have helped better interpret our findings. However, we speculate these factors may be implicated in the stiffening of central arteries following maximal exercise (Park et al 2012;Smith and Minson 2012;Smith et al 2015).…”
Section: Limitationsmentioning
confidence: 92%
See 1 more Smart Citation
“…activity, oxidative, or endothelial function for this study, which would have helped better interpret our findings. However, we speculate these factors may be implicated in the stiffening of central arteries following maximal exercise (Park et al 2012;Smith and Minson 2012;Smith et al 2015).…”
Section: Limitationsmentioning
confidence: 92%
“…Mechanisms underlying acute maximal exerciseinduced central arterial stiffening in obese individuals are unclear. Increases in sympathetic nerve activity have been associated with central arterial stiffening (Hart et al 2013;Smith et al 2015), and obese individuals have demonstrated increases in sympathetic nerve activity at rest and exaggerated sympathetic reactivity to stress (Kuniyoshi et al 2003;Park et al 2012;Huber and Schreihofer 2016). Obesity-related sympathetic overactivity has also been attributed to oxidative stress (Smith and Minson 2012), which increases postexercise in obese individuals (Vincent et al 2004), thus possibly contributing to central arterial stiffening (Chen et al 2012).…”
Section: Obesity Hemodynamics and Arterial Stiffness At Restmentioning
confidence: 99%
“…Previous studies have shown that LVH and carotid intima-media thickness are associated with raised BP (38,39). Another possible explanation is that skeletal muscle hypertrophy-related physical activity (e.g., resistance training) could increase arterial stiffness and activate the sympathetic nervous system (40,41), which may elevate BP in humans, according to previous studies (42,43). In addition, the diversity of muscle fiber type may also able to explain the relationships.…”
Section: Resultsmentioning
confidence: 86%
“…It has already been demonstrated that traditional high intensity strength exercise can acutely compromise flow-mediated vasodilation, reducing NOx levels in sedentary people. 18,19 In such a scenario, reduced nitric oxide bioavailability, combined with the high intensity, could be the result of two factors: increased sympathetic activation during exercise and consequent acetylcholine-mediated vasoconstriction 20 and increased muscle compression of blood vessels when large muscle groups are recruited. 19,20 In the present study, a significant reduction in SOD activity was observed in the LIBFR condition.…”
Section: Discussionmentioning
confidence: 99%